Introduction to the Special Issue on Sexual Orientation and Gender Identity in Counselling Psychology - Roughley, Robert A.; Morrison, Todd G. (Canadian Journal of Counselling and Psychotherapy, 2013)
It is imperative that those affiliated with the field of counselling psychology and allied health disciplines embrace affirmative practices when interacting with LGBT persons. This introduction to the special issue of the Canadian Journal of Counselling and Psychotherapy highlights the roles that theoretical and empirical work play in fulfilling this mandate.